Whole exome sequencing identifies the first STRADA point mutation in a patient with polyhydramnios, megalencephaly, and symptomatic epilepsy syndrome (PMSE). Issue 8 (12th May 2016) - Bi, Weimin; Glass, Ian A.; Muzny, Donna M.; Gibbs, Richard A.; Eng, Christine M.; Yang, Yaping; Sun, Angela
Abstract : Polyhydramnios, megalencephaly, and symptomatic epilepsy syndrome (PMSE) is an ultra rare neurodevelopmental disorder characterized by severe, infantile‐onset intractable epilepsy, neurocognitive delay, macrocephaly, and craniofacial dysmorphism. The molecular diagnosis of this condition has thus far only been made in 16 Old Order Mennonite patients carrying a homozygous 7 kb founder deletion of exons 9–13 of STRADA . We performed clinical whole exome sequencing (WES) on a 4‐year‐old Indian male with global developmental delay, history of failure to thrive, infantile spasms, repetitive behaviors, hypotonia, low muscle mass, marked joint laxity, and dysmorphic facial features including tall forehead, long face, arched eyebrows, small chin, wide mouth, and tented upper lip. A homozygous single nucleotide duplication, c.842dupA (p.D281fs), in exon 10 of STRADA was identified. Sanger sequencing confirmed the mutation in the individual and identified both parents as carriers. In light of the molecular discoveries, the patient's clinical phenotype was considered to be a good fit for PMSE. We identified for the first time a homozygous point mutation in STRADA causing PMSE. Additional bi‐allelic mutations related to PMSE thus far have not been observed in Baylor ∼6, 000 consecutive clinical WES cases, supporting the rarity of this disorder. Our findings may have treatment implications for the patient since previous studies have shown rapamycin as a potential therapeutic agent for the seizures and cognitive problems in PMSE patients. © 2016 Wiley Periodicals, Inc.